Appeals to Human Rights in the Context of Managing the COVID-19 Pandemic: Analysis of Government Hours in the Lithuanian Parliament in 2020–2021 - Valentinavičius, Vytautas; Morkevičius, Vaidas; Žvaliauskas, Giedrius; Briedienė, Monika (Politologija, 2022)
The securitization of the COVID-19 pandemic allowed governments in democratic countries to introduce extraordinary management measures that involved limiting various human rights. However, sound democratic governance always requires public debate on any policies introduced. These debates occur in multiple arenas and the parliament is among the most notable. In the context of human rights, some studies identified parliament as one of the most important agencies that promote human rights protection and oversee executive authorities (Lyer, 2019; Ncube, 2020). This article examines whether and how Lithuanian parliamentarians and government members addressed human rights during the Seimas debates when issues related to the COVID-19 pandemic were discussed. It investigates whether the Seimas could be considered an important agent contributing to the oversight of human rights in Lithuania. The article employs transcripts from the Seimas plenary debates as a data source, particularly speeches from the government question time from 2020.03 to 2021.01. The results of the qualitative thematic analysis revealed that human rights were generally not the main topic of the COVID-19 pandemic debates on the Seimas floor during government hours. It also showed that the attitudes of political parties toward specific human rights tended to shift when they switched from the opposition to the ruling majority and vice versa.